Beneficial Effects of Sulforaphane Treatment in Alzheimer's Disease May Be Mediated through Reduced HDAC1/3 and Increased P75NTR Expression - Zhang, Jingzhu; Zhang, Rui; Zhan, Zhipeng; Li, Xinhui; Zhou, Fuyuan; Xing, Aiping; Jiang, Congmin; Chen, Yanqiu; An, Li (Frontiers in Aging Neuroscience, 2017)
Alzheimer’s disease is an irreversible, progressive neurodegenerative disorder. The accumulation of Aβ in the brain is thought to play a causative role in the development of cognitive dysfunction in Alzheimer’s disease. The p75 neurotrophin receptor is of great importance to protect against the Aβ burden and its expression is regulated by histone acetylation. This study investigated whether the phytochemical sulforaphane, a pan-histone deacetylase inhibitor, up-regulates the p75 neurotrophin receptor expression via affecting histone acetylation in protection against Alzheimer’s disease. We found that sulforaphane ameliorated behavioral cognitive impairments and attenuated brain Aβ burden in Alzheimer’s disease model mice. Additionally, sulforaphane reduced the expression of histone deacetylase1, 2 and 3, up-regulated p75 neurotrophin receptor, and increased levels of acetylated histone 3 lysine 9 and acetylated histone 4 lysine 12 in the cerebral cortex of Alzheimer’s disease model mice as well as in Aβ-exposed SH-SY5Y cells. Furthermore, silencing of histone deacetylase1 and 3, but not histone deacetylase2, gene expression with small interfering RNA caused up-regulation of p75 neurotrophin receptor in SH-SY5Y cells. In conclusion, this study demonstrates that sulforaphane can ameliorate neurobehavioral deficits and reduce the Aβ burden in Alzheimer’s disease model mice, and the mechanism underlying these effects may be associated with up-regulation of p75 neurotrophin receptor mediated, apparently at least in part, via reducing the expression of histone deacetylase1 and 3.